(untitled) (Research, Society and Development, 2020)
The genetic improvement of poultry has been used in order to maximize the production of chicken meat. Thus, management techniques have stood out, as they improve profitability and reduce production costs, since they optimize the weight gain of birds and speed up slaughter. However, the accelerated weight gain can make the animals susceptible to metabolic disorders due to the lack of adaptation of the cardiorespiratory system whose functioning is related to room temperature and cardiac innervation. Thus, the objective of this study was to evaluate the influence of acute thermal stress on the heart of broiler chickens, evaluating the epicardium, the epicardial vessels and the quantitative, morphological, morphometric and histopathological aspects of the cardiac plexus. For that, 14 male animals were used, divided into two groups (n = 7): animals kept in an environment of thermal comfort (18oC) and animals in an environment of thermal stress (kept at 32o C in the 12 hours prior to slaughter). The results showed that thermal stress decreased the area of the adipocytes, the area and the length of the cardiac ganglia, increased the total collagen of the adipocytes and decreased the total collagen of the vessels and ganglia of the heart. It can be concluded that, in fact, acute thermal stress interfered in the parameters evaluated, since several histopathological changes were identified, such as the presence of lymphocyte infiltrates in the adipocytes of the epicardial tissue, edema, vascular congestion, fibrin infiltration in the cardiac plexus ganglia and ganglionitis.